Leader similarity and international sanctions - Jerg Gutmann; Pascal Langer; Matthias Neuenkirch (University of Hamburg, Institute of Law and Economics (ILE), 2025)
It is well-established that political leaders matter for domestic outcomes, but statistical evidence for their relevance in international politics is still scarce. Here, we ask whether the personal relationship between political leaders can change the propensity for nonviolent conflict between nation-states in the form of sanctions. Panel probit models with data for the period 1970 to 2004 are estimated to evaluate whether more similar leaders are less likely to sanction each other. Our results indicate that higher leader similarity significantly reduces the likelihood of sanction imposition. The effect is most pronounced for sanctions imposed through unilateral political decisions. The probability of such sanction imposition ranges from 4.9% at the highest observed leader similarity in the sample to 13.0% at the lowest. Leader similarity seems to matter especially for sanctions aimed at democratic change or human rights improvements, for non-trade sanctions, and when at least one autocracy is involved. Finally, leader similarity has become more important after the Cold War.
Keywords: D70; F51; K33; 330; Geoeconomics; International sanctions; Leader similarity; Political leaders